Exploring implementation challenges of decentralized clinical trials: A qualitative study of policy stakeholder perspectives in Denmark - Ida Hestbjerg; Ditte Bonde Stanek; Ulrik Bak Kirk; Christa Thomsen (Digital Health)
Background The implementation of decentralized clinical trials (DCTs) has received strong political interest in Denmark. Many policy stakeholders may directly or indirectly influence the implementation at a national strategic level. Diverging interests may drive the implementation process in different directions, which may result in an inefficient and unsustainable process. Objective The purpose of this study is to explore implementation challenges of DCTs by examining stakeholder interests that emerge in their accounts of the advantages and disadvantages of DCTs. Method This qualitative study is based on interviews with 15 participants from 12 institutions comprising patient institutions, healthcare institutions, industry institutions, and political institutions. All interviews were conducted between July and December 2023. Additionally, we included 13 policy documents. Interviews and documents were analysed twice. First, we conducted a data-driven thematic analysis. Second, we performed a second-order analysis informed by paradox theory. We used the concept of paradoxical tensions to understand the contradictions that occurred in the stakeholder accounts. Results To make the implementation of DCTs efficient and sustainable, the interests of stakeholders need to be aligned. However, our study demonstrated that the many different stakeholder interests created a knot of paradoxical tensions, which must first be resolved. Conclusion Policy stakeholders must collaborate to resolve the paradoxical tensions and align their different interests towards a common objective. The responsibility of the practical implementation process needs to be allocated to one stakeholder or a few stakeholders, who can guide the process.